Exfoliative vaginal cytology during the oestrous cycle of rusa deer (Cervus timorensis) - Mahre, Mohammed Bakari; Haron, Abd Wahid; Yusoff, Rosnina; Che' Amat, Azlan; Abdullah, Faez Firdaus Jesse (2012)
The vaginal epithelium is influenced by hormonal changes during the oestrous cycle, allowing cyclic monitoring of the various reproductive stages. The vaginal cytology of Cervus timorensis deer in Malaysia has not been reported before. This study investigated the pattern of vaginal exfoliative cytology to determine the reproductive status and by extension the ovarian function of Cervus timorensis deer hinds. Seventeen adult and healthy Cervus timorensis deer hinds were used in this research. Vaginal smears were collected twice weekly for three months by gently swabbing the vagina with a sterile cotton swab. Smears were transferred to 1-5 slides, air dried, and immediately fixed with 100% ethanol and stained with Giesma. Smears were examined under a light microscope at magnification of 400 X. Two hundred epithelial cells from each slide were evaluated and classified. Results of this research showed that the epithelial cells were present in the vaginal smears of the deer hinds throughout the cycle. In the smears from the cycling hinds, superficial cells were more frequently observed and they appeared to be associated with the proestrus, oestrus and early metoestrus phases of the cycle. We conclude that monitoring the cellular pattern of the vaginal epithelium of hind deer with natural oestrus is an efficient tool to determine the reproductive condition and by extension the ovarian function of the Cervus timorensis deer hinds.